Antioxidant Treatment with N-acetyl Cysteine Prevents the Development of Cognitive and Social Behavioral Deficits that Result from Perinatal Ketamine Treatment - Phensy, Aarron; Duzdabanian, Hasmik E.; Brewer, Samantha; Panjabi, Anurag; Driskill, Christopher; Berz, Annuska; Peng, George; Kroener, Sven (Frontiers in Behavioral Neuroscience, 2017)
Alterations of the normal redox state can be found in all stages of schizophrenia, suggesting a key role for oxidative stress in the etiology and maintenance of the disease. Pharmacological blockade of NMDA receptors can disrupt natural antioxidant defense systems and induce schizophrenia-like behaviors in animals and healthy human subjects. Perinatal administration of the NMDAR antagonist ketamine produces persistent behavioral deficits in adult mice which mimic a range of positive, negative, and cognitive symptoms that characterize schizophrenia. Here we tested whether antioxidant treatment with the glutathione precursor N-acetyl-cysteine (NAC) can prevent the development of these behavioral deficits. On postnatal days (PND) 7, 9 and 11 we treated mice with subanesthetic doses (30 mg/kg) of ketamine or saline. Two groups (either ketamine or saline treated) also received NAC throughout development. In adult animals (PND 70-120) we then assessed behavioral alterations in a battery of cognitive and psychomotor tasks. Ketamine-treated animals showed deficits in a task of cognitive flexibility, abnormal patterns of spontaneous alternation, deficits in novel-object recognition, as well as social interaction. Developmental ketamine treatment also induced behavioral stereotypy in response to an acute amphetamine challenge, and it impaired sensorimotor gating, measured as reduced prepulse inhibition of the startle response. All of these behavioral abnormalities were either prevented or strongly ameliorated by NAC co-treatment. These results suggest that oxidative stress is a major factor for the development of the ketamine-induced behavioral dysfunctions, and that restoring oxidative balance during the prodromal stage of schizophrenia might be able to ameliorate the development of several major symptoms of the disease.